Improving Tuberculosis Case Detection in Children: Summary of Innovations and Findings From 18 Countries - Rahman, Md. Toufiq; Malik, Amyn A; Amanullah, Farhana; Creswell, Jacob (Journal of the Pediatric Infectious Diseases Society, 2022)
Despite a growing focus on the plight of tuberculosis (TB) among children, 56% of the 1.2 million children who develop TB annually are not detected and notified. TB REACH is a platform of the Stop TB Partnership that supports innovative interventions to improve TB case detection and preventative treatment. We present summary findings from 27 TB REACH-supported projects in 18 countries. Interventions were designed around intensified case-finding approaches (facility-based systematic screening and contact investigation), capacity building (including decentralized care delivery and supported decision-making), and improving diagnostic methods (ie, introduction of alternative respiratory specimens and new tools to aid the diagnosis). These interventions were evaluated on how they worked to identify children with TB, prevent further transmission of TB among children, and strengthen the health system involved with childhood TB care. Overall, 13 715 children were detected with TB, improving case notifications by 34%. In addition, nearly 5000 eligible contacts were enrolled on TB preventive treatment through these interventions. Focusing efforts and funding on childhood TB can produce marked improvements in case detection.